2015
DOI: 10.3390/nu7095382
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Dietary Patterns and Impaired Fasting Glucose in Chinese Men: A Cross-Sectional Study

Abstract: Few studies have examined the association between Asian dietary pattern and prediabetes, in particular, the Chinese diet. We conducted a cross-sectional study to identify dietary patterns associated with impaired fasting glucose (IFG) which considered a state of prediabetes in Chinese men. The study included 1495 Chinese men aged 20 to 75 years. Information about diet was obtained using an 81-item food frequency questionnaire (FFQ), and 21 predefined food groups were considered in a factor analysis. Three diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 60 publications
2
19
0
Order By: Relevance
“…In addition, we established a robust association of adherence to prudent dietary pattern with abdominal obesity (OR = 0.63, 95%CI = 0.48–0.84) and abnormal fasting glucose (OR = 0.58, 95%CI = 0.35–0.94), by adding to the regression model both socio-demographic (i.e., marital status, employment and educational level) and behavioral factors (i.e., smoking, BMI, total energy intake and physical activity). Our results are in line with previous studies demonstrating the protective effect of healthy dietary patterns against the risk of central obesity [ 27 , 36 , 37 , 38 ], impaired fasting glucose [ 39 ], insulin resistance [ 40 ], and diabetes [ 41 ]. All these pathological features are also related to NAFLD and it has been similarly proved that adherence to a prudent dietary pattern reduced the risk of NAFLD [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we established a robust association of adherence to prudent dietary pattern with abdominal obesity (OR = 0.63, 95%CI = 0.48–0.84) and abnormal fasting glucose (OR = 0.58, 95%CI = 0.35–0.94), by adding to the regression model both socio-demographic (i.e., marital status, employment and educational level) and behavioral factors (i.e., smoking, BMI, total energy intake and physical activity). Our results are in line with previous studies demonstrating the protective effect of healthy dietary patterns against the risk of central obesity [ 27 , 36 , 37 , 38 ], impaired fasting glucose [ 39 ], insulin resistance [ 40 ], and diabetes [ 41 ]. All these pathological features are also related to NAFLD and it has been similarly proved that adherence to a prudent dietary pattern reduced the risk of NAFLD [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…(35) Diet was assessed based on food recall and calorie intake estimated using a software based on the Standard Tables of Food Composition in China. (36,37) All food and beverages taken in the previous day were recorded on three occasions: at screening visit, at baseline visit, and during a phone visit between the screening and baseline visit that was selected by the investigators. The 3 days in which information on diet was recorded included 2 weekdays and 1 Saturday or Sunday, with avoidance of major holidays or festivals.…”
Section: Measurements Of Diet and Physical Activitymentioning
confidence: 99%
“…To date, many epidemiological studies have examined dietary patterns in relation to T2DM and gestational diabetes mellitus (GDM) in China [11][12][13][14][15][16][17][18][19]. Only two published studies, however, have been reported on the association of dietary patterns with prediabetes in Chinese population [24][25]. Furthermore, to the best of our knowledge, no previous study has addressed the relationship between dietary patterns and risk of prediabetes in a middle-aged Chinese population.…”
Section: Introductionmentioning
confidence: 99%